Einstein on Einstein : autobiographical and scientific reflections - Gutfreund, Hanoch; Renn, Jürgen, 1956- (Princeton University Press, 2020)
"Einstein begins his Autobiographical Notes with one problem he never quite solved: "What, precisely, is thinking?" To answer, he turns inward to the very shape of his thoughts, the ongoing struggle to connect local observation, or what he calls the "momentary and personal," to the larger "mental grasp of things." Einstein situates his greatest discoveries amongst the other twentieth-century breakthroughs in the field and closely examines how these discoveries punctuated and propelled his own intellectual development. The autobiography expands what we know about Einstein's childhood education, readings in philosophy, and journey to the theory of general relativity. In this book, Autobiographical Notes is accompanied by introductions, essays, and commentary by Hanoch Gutfreud and Jürgen Renn, who draw on biographical information, written correspondence, and their knowledge of Einstein scholarship to render these difficult texts accessible to readers. They have also collected critical writings by Einstein's contemporaries alongside Einstein's own responses to these interlocutors, as well as Einstein's Autobiographical Sketch, composed just before his death in 1955, which is published for the first time in English"--